2018
DOI: 10.1080/13825585.2018.1451480
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of visual working memory and episodic memory performance in younger and older adults

Abstract: Working memory and episodic memory decline with age.  However, as they are typically studied separately, it is largely unknown whether age-associated differences are similar. A task design was developed in which visual working memory and episodic memory performances were measured using the same stimuli, with both tasks involving context binding. A 2-back working memory task was followed by a surprise subsequent recognition memory task that assessed incidental encoding of object locations of the 2-back task. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 58 publications
(87 reference statements)
6
19
0
1
Order By: Relevance
“…Comparable to Daselaar et al (2003), Sambataro et al (2012), Kalenzaga et al (2015), and Lugtmeijer et al (2019) found no age-related difference in recognition performance after incidental learning. Similarly, Aine et al (2005), Gutchess et al (2005), and Hämmerer et al (2018) found no evidence of a recognition deficit in older adults.…”
Section: Resultsmentioning
confidence: 69%
“…Comparable to Daselaar et al (2003), Sambataro et al (2012), Kalenzaga et al (2015), and Lugtmeijer et al (2019) found no age-related difference in recognition performance after incidental learning. Similarly, Aine et al (2005), Gutchess et al (2005), and Hämmerer et al (2018) found no evidence of a recognition deficit in older adults.…”
Section: Resultsmentioning
confidence: 69%
“…Campbell and Hasher (2018) showed that the effect of hyper-binding in older adults disappears when made aware of the connection between the tasks. Finally, our previous study in which we studied the effect of age on memory with this task design, did not show an advantage for older adults on the subsequent memory task (for a more extensive discussion on the task design see Lugtmeijer et al 2019).…”
Section: Discussionmentioning
confidence: 89%
“…To assess visual working memory, an N-back task with common objects was employed (for more details on the task see Lugtmeijer et al 2019). In short, during the 2-back task, stimuli are presented in serial presentations and participants identify stimuli that are identical to a stimulus presented 2 trials before.…”
Section: Memory Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…忆这一核心认知功能上, 尽管使用中性材料的研 究 均 发 现 工 作 记 忆 表 现 出 随 增 龄 下 降 的 特 点 (Brockmole & Logie, 2013;Lugtmeijer et al, 2019) (Peng et al, 2018;Swanson & Fung, 2016) Addis et al, 2010;Kalenzaga et al, 2016;Scheibe & Carstensen, 2010)。现有研究发现, 当工作记忆 Bermudez & Souza, 2017;Majerus & D'Argembeau, 2011;Mammarella et al, 2013), 而当任务相关刺 激为情绪面孔时积极效应则表现为老年人对消极 刺激的记忆减弱 (Mok et al, 2019;Sava et al, 2017;Svärd et al, 2014…”
Section: )。近年来对积极效应的考察拓展到工作记unclassified